2021
DOI: 10.1108/ajems-05-2020-0228
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the nonlinear effect of size on profitability: evidence from an insurance brokerage industry in an emerging market

Abstract: PurposeThis study examines the possible nonlinear effect of size on stakeholder and shareholder profitability in the Ghanaian insurance brokerage industry.Design/methodology/approachThis study employs a panel dataset of 64 Ghanaian insurance brokerage firms spanning 2011–2015. Static [ordinary least squares (OLS), fixed effect and random effect and dynamic (two-step generalized method of moments (GMM))] estimation techniques are employed to analyze the data.FindingsThe study finds the existence of both economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…Likewise, the positive relationship between SIZE and ROE-which represents a percentage rise in SIZE is associated with about a 0.833 percent increase in ROE. The result also supports the previous findings of Kotey et al (2021), who confirm that firm size increments Firm Performance Indicators as a Fundamental Analysis of Stocks and a Determinant of a Firm's Operation 204 positively affect stakeholder and firm performance. This finding was also confirmed by Ayaz et al (2021).…”
Section: Ordinary Least Square and Quantile Regression Analysissupporting
confidence: 90%
See 3 more Smart Citations
“…Likewise, the positive relationship between SIZE and ROE-which represents a percentage rise in SIZE is associated with about a 0.833 percent increase in ROE. The result also supports the previous findings of Kotey et al (2021), who confirm that firm size increments Firm Performance Indicators as a Fundamental Analysis of Stocks and a Determinant of a Firm's Operation 204 positively affect stakeholder and firm performance. This finding was also confirmed by Ayaz et al (2021).…”
Section: Ordinary Least Square and Quantile Regression Analysissupporting
confidence: 90%
“…Firstly, factor that determine profitability (firm's performance) is firm size (Akotey et al, 2013;Kotey et al, 2021). According to the results of Liargovas and Skandalis (2010), financial leverage, firm size, liquidity ratio and operational ability have a significant impact on a firm's competitiveness, which can be measured using three variables: ROA, ROE and sales.…”
Section: The Determinant Of Firm Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Empirically, extant studies have identified a two‐way relationship between bank size and profitability (Akinlo, 2012b; Bolarinwa & Obembe, 2017; Olaniyi, Olayemi, et al, 2017). A more dominant strand in the literature asserts that bank size plays a key and decisive role in driving the profitability and efficiency of listed banks (Kotey et al, 2021). It is conceptualized that increasing bank size can induce an increase in profitability and efficiency by spurring banks to enjoy economies of scale and scope (Shepherd, 1972).…”
Section: Introductionmentioning
confidence: 99%